Maternal Agreeableness Moderates Associations Between Young Children's Emotion Dysregulation and Socioemotional Functioning at School. Issue 2 (4th March 2017) - Hipson, Will E.; Gardiner, Sarah L.; Coplan, Robert J.; Ooi, Laura L.
ABSTRACT: The goal of this study was to explore associations among maternal agreeableness, child temperament (i.e., emotion dysregulation), and children's social adjustment at school. Participants were 146 children in kindergarten and Grade 1 (76 girls; M age = 67.78 months, SD = 10.81 months). Mothers provided ratings of their own agreeableness and their child's temperament, and teachers assessed indices of children's socioemotional functioning at school. Among the results, maternal agreeableness moderated associations between child dysregulation and aspects of adjustment at school. Specifically, at higher levels of maternal agreeableness, the relations between child dysregulation and both anxiety with peers and their prosocial behavior were attenuated. Overall, the results suggest that maternal agreeableness may serve as a protective factor for dysregulated children. Implications for research and practice are discussed.